Differential roles for Fos and Jun in DNA-binding: redox-dependent and independent functions. - Ng, L (1993)
The Fos and Jun family of transcription factors contain an invariant sequence motif lysine-cysteine-arginine (KCR) in the highly conserved DNA-binding region. Reduction of the cysteine residue is necessary to facilitate DNA-binding. Here, we examined the potential dual roles of the flanking lysine and arginine residues in influencing the redox reactivity of the cysteine and the DNA-binding activity of Fos and Jun. Two sets of Fos and Jun mutants were generated: the KCR and KSR series representing proteins capable of redox-dependent and redox-independent DNA-binding activity, respectively. Mutation of the lysine in Fos-Jun heterodimers had no obvious effect on the redox reactivity of the cysteine, suggesting that lysine is not essential in this respect. However, mutation of the arginine but not lysine, in both the KCR and the KSR series abolished DNA-binding activity. Thus, the arginine but not the lysine residue in the KCR motif is critical for both redox-dependent and redox-independent functions in DNA-binding. Surprisingly, the triple substitution, ISI, exhibited high levels of DNA-binding activity. This demonstrates that the effects of amino acid substitutions can be highly dependent on context and that non-basic amino acids can function efficiently in DNA-binding. Analysis of combinations of wild-type and mutant Fos and Jun proteins indicated that Fos was dominant in dictating the DNA-binding ability of Fos-Jun heterodimers. This suggests that the lysine and arginine residues in the KCR region of Fos are not equivalent to those in Jun and that they interact with DNA differently.